HORMONE PROFILE IN SURTI GOATS DURING POSTPARTUM PERIOD - Chaudhary, Sandhya; Singh, Virendra Kumar; Patel, Sanjay B (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken to investigate changes in serum hormonal profile of post partum Surti goats. 20 recently parturated (treatment) goats and 20 non pregnant (control group) goats. Blood samples were collected from treatment group on 0, 7, 14, 21, 30 and 45 day post kidding and once from control group. Serum samples were analyzed for Tri-Iodothyronine (T3) and Tetra Iodothyronine /Thyroxine (T4), cortisol, progesterone (P4) and estradiol, T4 and P4 were significantly low whereas cortisol and estradiol levels were significantly high on 0 day post partum. Onset of kidding was marked by increased cortisol and estrogen and decreased progesterone.